The revival of critical thinking and creativity in Muslim societies - Abdul Razak, Mohd Abbas; Abdullah, Norillah (IslamiCity, 2024)
Experts in psychology and creativity agree that creativity can be taught and learned. The outdated belief that creativity is an inborn talent exclusive to a select few is no longer valid. Recent research highlights that creativity exists both within individuals and in the environments around them. Taking a middle path, we believe that while creativity is embedded in the human spirit, there are times and situations in a person's external world when the environment inspires him or her to be creative. There is significant potential for discovering innovative ideas through hands-on experimentation and a trial-and-error approach to learning, enabling individuals to solve various human problems creatively. Creativity is not just an inborn talent; it manifests across various aspects of life. It can be expressed through culinary skills, architecture, engineering, fine arts, poetry, literature, interior design, floral arrangements, visual art, music, and more. This versatility highlights the broad scope of creativity, showcasing its presence in both everyday activities and specialized fields. Throughout the history of Islamic education, Muslim scholars and philosophers have supported the importance of creativity in education. Prominent scholars and philosophers like Al-Farabi (872-950), who was nicknamed the 'Second Teacher' after Aristotle; Ibn Sina (980-1037), who was popularly known as a medical doctor, philosopher, and psychologist; Al-Ghazali (1058-1111), a prominent theologian, philosopher, and Sufi master; Ibn Khaldun (1332-1406), the historian and philosopher who wrote the 'Muqaddimah' Ibn Rushd (1126-1198), an influential philosopher and commentator on Aristotle; Rumi (1207-1273), the famous mystic-poet of the East and West; and Iqbal (1877-1938), the mystic-philosopher who wrote 'The Reconstruction of Religious Thought in Islam', have all spoken in favour of creativity in Muslim education.